(untitled) - Zonyane-Egbichi, Samkele

Metabolomic analysis, genetic analysis and biological activities of Lessertia Frutescens (L.) Goldblatt & J.C. Manning populations in South Africa (Stellenbosch : Stellenbosch University, 2022)
Thesis (PhD)--Stellenbosch University, 2022.